Pengaruh Paket Pupuk Organik, Anorganik dan Pupuk Hayati Terhadap Sifat Tanah dan Hasil Tanaman Kangkung Darat (Ipomea reptana Poir) pada Tanah Vertisol - VANDANI, YAYAN; KUSMIYARTI, TATI BUDI; SUSILA, KETUT DHARMA (Agrotrop : Journal on Agriculture Science; Vol 10 No 2 (2020), 2020)
The effect of Organic, Inorganic and Biofertilizer Package on the Properties of Soil and Yield of Land Kale on the Vertisol . This study aims to determine the effect of organic, inorganic and biofertilizer packages on the soil properties and yield of land kale (Ipomea reptana Poir) on the Vertisol. The experiment used a Randomized Block Design (RBD) with 6 treatments and 4 replications. Parameters observed consisted of total-N, available-P, available-K, organic-C, cation exchange capacity (CEC), base saturation, pH, permeability, bulk density, total microorganism, plant height, fresh weight of plants and oven dry weight. Statistical analysis using univariate, the effect of treatment seen based on the F test, if the treatment has a significant effect then proceed with the LSD test level of 5%. The results of variance analysis showed that the effect of the package of organic, inoganic and biofertilizers had a very significant effect on the  parameters of organic C, significantly effected the available-P of the soil and did not significantly effect the total-N, CEC, base saturation, pH , permeability, bulk density, total microorganism, and no significant effect on the parameters of land kale.